ESG disclosure in the palm oil industry: a comparative study of Malaysia and Indonesia - Mad, Salina; Mohd Suffian, Mohd Taufik; Omar, Nor Alwani (UiTM Cawangan Johor, 2025)
This study examines the differences in ESG reporting practices among Malaysian and Indonesian palm oil companies. The palm oil sector is often criticized due to its environmental and social issues, which subsequently leads to an increase in pressure from stakeholders for it to act responsibly. Hence, ESG disclosure plays an important role in the palm oil sector to manage its stakeholders' pressure. The differences in regulatory approaches, institutional practices, and certification schemes of the ESG disclosure in both countries are expected to influence firms’ disclosure behaviour. This study examines 24 listed palm oil companies over the 2020-2024 period by using the secondary data from the ZLS SPOTT and LSEG Workspace. Independent t-test and pooled ordinary least squares regression are employed to analyse the influence of country–level differences on ESG disclosure practices. The findings show that the social pillar is the largest contributor to overall ESG scores across the industry. This indicates that the labour and community pillar was the priority in firms’ resource allocation and sustainability reporting efforts. Although ESG disclosure levels are generally similar for both countries, however, Malaysian firms exhibit significantly higher disclosure levels on the governance pillar. These findings offer useful insight for investors to make comparisons between the two markets and help firms and policymakers to identify opportunities for improvement in ESG disclosure across the palm oil industry.